2018
DOI: 10.1002/app.46556
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels based on alkylated chitosan and polyelectrolyte copolymers

Abstract: Hydrogels formed by alkylated chitosan with N‐(3‐chloro‐2‐hydroxypropyl) trimethylammonium chloride and synthetic copolymers forming polyelectrolyte complexes are presented. The copolymer polyelectrolytes were synthesized through free‐radical polymerization. Their compositions and reactivity parameters were determined by the Finemann–Ross and Kelen–Tüdos methods. The copolymers have structures that tend to be alternating. The hydrogels were characterized by thermogravimetric analysis, Fourier transform infrare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…The functionalization of chitosan was performed with 0.5 g of commercial chitosan that was previously subjected to a deacetylation process following the methodology of Palacio et al 35 Later, for the alkylation process, N ‐(3‐chloro‐2‐hydroxypropyl) trimethylammonium chloride was used, with 0.5 g of previously deacetylated chitosan and following the methodology proposed by Jiang et al 36 and Sajomsang et al 37 The purification of the functionalized chitosan was performed using cellulose bags (Sigma‐Aldrich) with a molecular weight cutoff (MMCO) of 12 to 14 kDa in double distilled water for 48 hours with water exchange every 6 hours. Subsequently, the obtained chitosan was frozen and subjected to a lyophilization process for characterization.…”
Section: Methodsmentioning
confidence: 99%
“…The functionalization of chitosan was performed with 0.5 g of commercial chitosan that was previously subjected to a deacetylation process following the methodology of Palacio et al 35 Later, for the alkylation process, N ‐(3‐chloro‐2‐hydroxypropyl) trimethylammonium chloride was used, with 0.5 g of previously deacetylated chitosan and following the methodology proposed by Jiang et al 36 and Sajomsang et al 37 The purification of the functionalized chitosan was performed using cellulose bags (Sigma‐Aldrich) with a molecular weight cutoff (MMCO) of 12 to 14 kDa in double distilled water for 48 hours with water exchange every 6 hours. Subsequently, the obtained chitosan was frozen and subjected to a lyophilization process for characterization.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they possessed good coagulation efficiency, which was confirmed by in vitro blood coagulation experiments. Palacio et al [ 81 ] prepared alkylated chitosan and N -(3-chloro-2-hydroxypropyl) trimethylammonium chloride through free radical polymerization. Chen et al [ 82 ] designed a series of N-alkylated chitosan (NACS) samples with different chain lengths and substitution degrees (SD) of alkyl groups.…”
Section: Chitosan-based Hydrogel Dressingsmentioning
confidence: 99%
“…Thus, the literature indicates the adsorption of antibiotics such as ciprofloxacin [113], erythromycin, amoxicillin [242], amicacin [243], tylosin, norfloxacin [244], among others, in which adsorption was established as high capacity. Chitosan, being a polysaccharide that has different characteristics such as being biocompatible, presenting biodegradability and antibacterial activity [245,246] it has been shown that its use exhibits better properties than other commercial pearls or microbeads [247] and can adsorb potentially toxic compounds [248]. The literature mentions that the use of chitosan either in the form of chitosan beads [249], chitosan-carbon pearls [250] chitosan resin pearls [251] etc.…”
Section: Removal Of Amoxicillin By Chitosanmentioning
confidence: 99%